Policy Analysis on China’s PVs Policies from 2012 to 2022: A Content Analysis - Chen, Yu; Jiang, Wen (Journal of Theory and Practice of Social Science, 2023)
As an abundant and renewable energy source, photovoltaic solar energy has garnered substantial investments over the past decade, emerging as a pivotal tool in the global effort to decarbonize. In this process, China has transitioned from being primarily an "Original Equipment Manufacturer (OEM)" for Western countries in the photovoltaic industry to a key player in the global photovoltaic landscape. This transformation has significantly reshaped the global supply and demand dynamics for photovoltaic products. This research employs a combination of qualitative and quantitative content analysis methods to categorize and analyze 192 policy documents issued by the central government of China between 2012 and 2022. By scrutinizing policy action areas, policy instruments, and policy targets, this paper elucidates China's nationally led, top-down approach to photovoltaic development. The goal is to offer an overarching perspective on the types and evolution of PV policies implemented by the Chinese central government. This study addresses gaps in knowledge within the realm of Chinese decarbonization and offers pertinent policy recommendations.